DIGITAL TRANSFORMATION IN EDUCATIONAL MARKETING MANAGEMENT - Rhamadan, Sultan Fhajar; Dina Veronica (International Journal of Multidisciplinary Reseach, 2025)
Digital transformation in marketing management is the process of integrating digital technology into a company's marketing strategy. It involves changes in marketing strategies, processes, and organizations, allowing businesses to improve data management, formulate effective marketing strategies, and increase public awareness of products. In addition, the company's interaction with customers and markets has also changed thanks to digital technology. Digital marketing has replaced conventional methods, offering a more efficient way to reach a wider audience. Branding on social media has become important in building an image and increasing interaction with consumers. This study uses a qualitative method through literature study to collect relevant information on the role of education in personality formation and emphasizes the importance of innovation in digital marketing strategies in an era of intense competition. Automation in educational administration is also highlighted, considering the technology that influences the way students learn and interact.